Factors related to contact dermatitis in Makassar City salons - Alya Farhana Bumulo; Nurgahayu Nurgahayu; Nasruddin Syam (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: contact dermatitis is an inflammation of the skin, generally induced by exposure to extrinsic irritants and allergens. Based on direct interviews conducted by researchers, some salon workers experience contact dermatitis. Symptoms are experienced in the form of small bubbles filled with liquid on the palms of the hands, the skin on the palms feels dry and peeling, and the palms are red and sore due to frequent contact with materials found in the salon. Objective: To determine the factors associated with contact dermatitis in Makassar city salons. Methods: This study used quantitative research methods with a cross-sectional approach. The population in this study was 60 respondents from 7 salons. The sample in this study was 40 workers. The instrument used was a questionnaire. Data analysis using univariate and bivariate analysis. Result: showed that there was a relationship between working period and contact dermatitis (p-value = 0.043 < 0.05), there was a relationship between length of contact with contact dermatitis (p-value = 0.022 < 0.05), there was no relationship between personal hygiene with contact dermatitis (p-value = 1.000 > 0.05), there was no relationship between the use of personal protective equipment (PPE) with contact dermatitis (p-value = 0.638 > 0.05). Conclusion: There is a relationship between the length of work and the length of contact dermatitis in salon workers. It is recommended that salon workers use moisturizer after washing their hands to coat the skin's surface and prevent water loss. Moistors can also be applied to the area affected by dermatitis, which keeps the skin moist so that the recovery process will be faster. Make sure to use a fragrance-free, alcohol-free moisturizer, and hypoallergenic so as not to irritate the skin even more.